2008
DOI: 10.1128/aem.02268-07
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Odors from Swine Wastewater by Using Microbial Fuel Cells

Abstract: A single-chamber microbial fuel cell (MFC) was used to reduce 10 chemicals associated with odors by 99.76% (from 422 ؎ 23 g/ml) and three volatile organic acids (acetate, butyrate, and propionate) by >99%. The MFC produced a maximum of 228 mW/m 2 and removed 84% of the organic matter in 260 h. MFCs were therefore effective at both treatment and electricity generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(57 citation statements)
references
References 28 publications
3
51
1
2
Order By: Relevance
“…Kim et al [13] produced 228 mW/m 2 of electric energy at an electric potential of 0.4 V from 165 ml in a singlechambered MFC with 1,000 Ω of external resistance, consuming about 6,946 mg/l of COD. Jia et al [12] reported that 1.7 mW/m 2 of electric energy was produced by an MFC using denitrifying bacteria as an electron acceptor with a coulombic efficiency of 7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [13] produced 228 mW/m 2 of electric energy at an electric potential of 0.4 V from 165 ml in a singlechambered MFC with 1,000 Ω of external resistance, consuming about 6,946 mg/l of COD. Jia et al [12] reported that 1.7 mW/m 2 of electric energy was produced by an MFC using denitrifying bacteria as an electron acceptor with a coulombic efficiency of 7%.…”
Section: Discussionmentioning
confidence: 99%
“…Phone: +82-2-940-7190; Fax: +82-2-919-0345; E-mail: baakdoo@skuniv.ac.kr [13] used a single-chamber MFC to remove odors from swine wastewater. MFCs have also been used for ammonium oxidation and biological denitrification, in which the reducing power generated by exoelectrogenic bacteria may be converted to metabolic energy by denitrifying bacteria [5,6].…”
Section: *Corresponding Authormentioning
confidence: 99%
“…A variety of wastewater have been used in MFC as fuel such as domestic sewage with voltages ranging from 0.43-0.44 V (Ahn and Logan, 2010) and 0.32±0.01 V (Liu et al, 2004);Huang and Logan, 2008 were able to produce the power output of 400 mV -420 mV using paper and pulp wastewater; maximum voltages generated in an MFC using Rice mill wastewater were 0.304 V and 0.172 V (Behera et al, 2010); brewery wastewater was able to produce 0.071 -0.330 V (Feng et al, 2008); a current of 2.12-2.48 mA were recorded using distillery wastewater (Mohanakrishna et al, 2010); in odor-producing compounds treatment of swine wastewater a maximum of 0.4 V were recorded (Kim et al, 2008); Oil refinery wastewater produced the maximum voltage output of 0.355 V (Majumder et al,2014). A maximum open-circuit potential of 2.2 V was obtained using rice mill wastewater with the anode in batch-fed mode of operation (Daniel et al, 2009); 0.4908 V achieved using starch processing wastewater (Lu et al, 2009); 0.421V was produced using starch processing wastewater (Park et al, 2001), 0.207±0.03 V to 0.350±0.025 V were recorded using municipal Wastewater (Mohanakrishna et al, 2010); high open circuit voltage (OCV) of 0.810 V were reported using dairy industry wastewater (Lu et al, 2009), 0.689 V was generated using coconut husk retting wastewater (Park et al, 2001), near 1 V open circuit potential (OCV) were (Baranitharan et al, 2013).…”
Section: Bioelectricity Production By Indigenous Anodereducing Bactermentioning
confidence: 99%
“…A variety of wastewater has been used in MFC as fuel such as domestic sewage (Ahn and Logan, 2010;Liu et al, 2004), paper and pulp (Huang & Logan, 2008), rice mill (Behera et al, 2010), brewery (Feng et al, 2008), swine wastewater (Kim et al, 2008) and phenolic wastewater (Luo et al, 2009) , Oil refinery wastewater (Majumder et al, 2014), Effluent rice mill wastewater (Daniel et al, 2009), chocolate industry wastewater (Patil et al, 2009), and real dye wastewater (Kalathil et al, 2012) etc.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] In most cases, they used raw swine wastewater as inoculum as well as substrate after removing large particles. Maximum power densities in the range of 200 and 260 mW/m 2 using full-strength wastewater were obtained.…”
mentioning
confidence: 99%